2002
DOI: 10.1081/hem-120015028
|View full text |Cite
|
Sign up to set email alerts
|

Hb G-MAKASSAR [β6(A3)Glu→Ala; CODON 6 (GAG→GCG)]: MOLECULAR CHARACTERIZATION, CLINICAL, AND HEMATOLOGICAL EFFECTS

Abstract: We report a Thai family in which five members are Hb G-Makassar heterozygotes and one member is, in addition, a heterozygote for beta0-thalassemia (IVS-I-1, G-->T). We confirm that the previously presumed mutation at codon 6 of the beta-globin gene is GAG-->GCG. Hb G-Makassar heterozygotes are asymptomatic and hematologically normal. The Hb G-Makassar/beta0-thalassemia compound heterozygote has features of thalassemia minor. A simple and rapid polymerase chain reaction-restriction fragment length polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
6
26
0
Order By: Relevance
“…Another 7 variants, Hb C, Hb D-Punjab, Hb G-Makassar, Hb Q-Thailand, Hb Lepore-Hollandia, and Hb Hope, have been reported in all parts of Thailand [14,16,[27][28][29][30][31], but due to difference in race and ethnicity, the prevalence differs (data were shown in Table 4). As there is a high prevalence of Hb C in the southern Thai population, nearly 50% of it was found in the samples in spite of very few cases being found in other parts of Thailand [16,32].…”
Section: Discussionmentioning
confidence: 96%
“…Another 7 variants, Hb C, Hb D-Punjab, Hb G-Makassar, Hb Q-Thailand, Hb Lepore-Hollandia, and Hb Hope, have been reported in all parts of Thailand [14,16,[27][28][29][30][31], but due to difference in race and ethnicity, the prevalence differs (data were shown in Table 4). As there is a high prevalence of Hb C in the southern Thai population, nearly 50% of it was found in the samples in spite of very few cases being found in other parts of Thailand [16,32].…”
Section: Discussionmentioning
confidence: 96%
“…Many Hb variants with similar electrophoretic mobilities or HPLC profiles with those of Hb Q-Thailand and Hb QE have been reported in Asian populations e.g. Hb Tak, Hb D-Punjab, Hb S, Hb Korle-Bu, Hb Siam and Hb G-Makassar (17)(18)(19)(20)(21)(22)(23)(24). Interaction of these abnormal Hbs with other hemoglobinopathies and thalassemias can cause serious conditions (25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, at least seven Hb variants have been identified with the retention times in the HbA 2 window. These include HbE, Hb Lepore ( δ β ‐hybrid variant) (15), Hb Korle‐Bu (16), Hb D‐Panjab (17), Hb Tak (18, 19), Hb G‐Makassar (20) and Hb Woodville in this study, all have been reported from Thailand, making the diagnosis of such variants more confounding. Therefore, the HPLC only distinguish the presence of some frequent variants but results might be less obvious for rare variants and the use of an additional method is always required (21).…”
Section: Discussionmentioning
confidence: 85%